What public health interventions do people in Canada prefer to fund? A discrete choice experiment - Kiffer G. Card; Marina Adshade; Robert S. Hogg; Jody Jollimore; Nathan J. Lachowsky (BMC, 2022)
Abstract Objective To assess public support of tailored and targeted public health interventions for marginalized communities. Methods We conducted a discrete choice experiment using a web-based survey advertised to Facebook and Instagram users living in Canada, aged > 16. Participants were asked to choose between funding two hypothetical public health programs. Each program was described by its purpose; expected increase in life expectancy; and target audience. Demographically weighted generalized linear mixed-effects models were constructed to identify program factors associated with program selection. Results Participants completed up to 8 discrete choice comparison exercises each resulting in 23,889 exercises were completed by 3054 participants. Selected programs were less likely to focus on prevention (vs. treatment). For each 1-year increase in the marginal years of life gained, there was a 15% increase in the odds of a program being selected. Interventions tailored to marginalized communities or targeting stigmatized health conditions were less likely to be selected compared to interventions targeted to the general population or targeting chronic health conditions. Noteworthy exceptions included an increased preference for interventions aligning with the perceived needs or cultural expectations for marginalized communities. Conclusions Stigmatizing perceptions of health conditions and key populations likely influence public health programming preferences of Canadians. Public health implications Informational campaigns highlighting disparities experienced by marginalized populations may improve support for targeted and tailored interventions.